Liquid metal droplet dynamics - Xi Zhao; Mengwen Qiao; Yingxin Zhou; Jing Liu (Droplet, 2024)
Abstract The unique properties to combine the dual merits of both liquids and metals together make the gallium‐based liquid metal (LM) droplets a class of unconventional substitute which possess great potential for a group of newly emerging areas, such as stretchable electronics, soft devices, micro sensors and actuators. In addition, LM droplets are undoubtedly an intriguing target worth of pursuing in fundamental hydrodynamic investigations due to their extremely high surface tension nature compared to classical nonmetallic fluids. Since the discovery of the diverse transformation phenomena and self‐fueled droplet mollusks of LM that can move automatically in solution via single electricity or even without any external energy supply, tremendous attentions were attracted to this special fluidic object of LM droplets. Over the past decade, there has been a proliferation of explorations on LM droplet dynamics, while the involved contents are heterogeneous due to the interfacial physical/chemical activity of the LM and the diversity of the kinetic behaviors. To better understand and manipulate the droplet behavior and to promote further development of the LMs, this review is dedicated to summarize the latest progress and presents an overview on basic findings related to LM macro‐droplet dynamics. Firstly, the extended definition of LM droplets and the corresponding fabrication methods are given. Then, typical works on LM droplet dynamics are systematically interpreted based on their different behavior categories. Finally, the perspectives, main obstacles and challenges restricting the development of LM droplet dynamics are pointed out.